Who deserves to die : constructing the executable subject - Sarat, Austin; Shoemaker, Karl. (Amherst : University of Massachusetts Press, 2011)
Death penalty scholars "assess the forms of legal subjectivity and legal community that are supported and constructed by the doctrines and practices of punishment by death in the United States. They help us understand what we do and who we become when we decide who is fit for execution."--Back cover.
What kind of self is the executable subject? -- The medieval origins of the Supreme Court's prohibition on executing the insane / Karl Shoemaker -- The unlucky psychopath as death penalty prototype / Robert Weisberg -- Waiving from death row / Susan R. Schmeiser -- No remorse / Ravit Reichman -- Constructing the executable subject: sacrifice and the rituals of State killing -- The unsacrificeable subject? / Mateo Taussig-Rubbo -- Last words: structuring the State's power to punish / Vanessa Barker -- The meaning of death: last words, last meals / Linda Ross Meyer -- New perspectives on selfhood and the purposes of capital punishment -- Executing retributivism: Panetti and the future of the eighth amendment / Dan Markel -- Therapeutic death / Ruth A. Miller -- The dead, the human animal, the executable subject / Thomas L. Dumm.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Capital punishment -- Moral and ethical aspects -- United States; Discrimination in capital punishment -- United States; Peine de mort -- Aspect moral -- États-Unis.; Discrimination dans l'application de la peine de mort -- États-Unis.; SOCIAL SCIENCE -- Criminology; Capital punishment -- Moral and ethical aspects; Discrimination in capital punishment; United States